KONSTRUKSI ARBEIT DALAM SASTRA JERMAN PASCAREUNIFIKASI - Syamsu Rijal (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2016)
Simultaneous post-reunification with the presence of the New Economy era has brought Germany entered a new phase, especially in the economic field (read: Arbeit). The manufacturing sector which previously controlled the labor market in Germany has been shifted by the services sector (Dienstsleistungsbereiche). Utilization of the latest technology and the power of innovation become key to success. This had an impact on the changing structure of work world (Strukturwandel der Arbeitswelt) in Germany. In this era, Arbeit has been transformed into